Intravitreal injection of a Rho-kinase inhibitor (fasudil) combined with bevacizumab versus bevacizumab monotherapy for diabetic macular oedema: a pilot randomised clinical trial. Issue 7 (27th August 2018) - Ahmadieh, Hamid; Nourinia, Ramin; Hafezi-Moghadam, Ali; Sabbaghi, Hamideh; Nakao, Shintaro; Zandi, Souska; Yaseri, Mehdi; Tofighi, Zahra; Akbarian, Shadi
Abstract : Background/aims: To compare the efficacy of combined intravitreal injection of bevacizumab and a Rho-kinase inhibitor, fasudil (intravitreal bevacizumab (IVB)/intravitreal fasudil (IVF)), with IVB alone for centre-involving diabetic macular oedema (DME). Methods: In this prospective randomised clinical trial, 44 eyes with centre-involving DME were randomised into two groups. The combined group received three consecutive injections of IVB (1.25 mg) and IVF (50 µM/L) monthly, while the monotherapy group received only one IVB (1.25 mg) injection per month for 3 months. Changes in best-corrected visual acuity (BCVA) and central macular thickness (CMT) were compared between the two groups at months 3 and 6. The primary outcome measure was the mean change in BCVA at month 6. Results: Mean BCVA was significantly improved in both groups at month 3 (P<0.001), but it persisted up to month 6 only in the IVB/IVF group. Improvement of BCVA was greater in the IVB/IVF group at both time points (P=0.008, P<0.001). In the IVB/IVF and IVB groups, 54.5% versus 10% of the eyes gained≥15 ETDRS letters at month 6 (P=0.026). Between months 3 and 6, mean BCVA significantly decreased by 5±7 ETDRS letters in the IVB group (P=0.002), while no significant deterioration was observed in the IVB/IVF group. Corresponding with the BCVA changes, CMT was significantly reduced in both groups at month 3 (p=0.006, p<0.001) but this reduction sustained only in the IVB/IVF group up to month 6 (p<0.001). Conclusion: Adjunctive intravitreal injection of a Rho-kinase inhibitor may enhance and prolong the therapeutic effects of anti-vascular endothelial growth factor drugs for centre- involving DME.